Typology and Iconography of Secular Scenes in the Decoration of Wooden Objects of mid 11th — beginning of the 14th Century from Archeological Excavations in Novgorod the Great: Problem Statement - Slapinia, Anna A. (Actual Problems of Theory and History of Art, 2015)
The article is focused on not so well-known wooden objects of minor arts that were found during archeological excavations in Novgorod. Those objects are decorated with “secular” figurative scenes — images that do not contain religious iconographic schemes. We don’t have many examples of Old Russian secular art, that’s why each archeological finding is very important. The relevance of our research is based on the fact that those objects are usually studied with archeological methods. For the first time we investigated their decor with iconographic method. For this research we divided our material into four iconographic groups and selected for each one several analogues from the circle of Scandinavian, Western European and Byzantine art. As a result we found most popular medieval iconographic schemes adopted by local artists. The fact that those schemes were used in Novgorod proves the importance of studying this archeological material in cultural and cross-cultural researches on the Middle Age.
Keywords: iconography; archeology; minor arts; Novgorod; woodworking